Correlations Between Ultrasonographic Findings of Invasive Lobular Carcinoma of the Breast and Intrinsic Subtypes - Wen, Xin; Yu, Yingjiao; Yu, Xiwen; Cheng, Wen; Wang, Zhuozhong; Liu, Lin; Zhang, Lei; Qin, Ling; Tian, Jiawei (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose To analyze the ultrasonographic findings of invasive lobular carcinoma (ILC) of the breast in 360 women and the correlations between the characteristics and the intrinsic subtypes.Materials and Methods We evaluated the imaging findings according to the lexicon of the American College of Radiology Breast Imaging Reporting and Data System (BI-RADS). The included ultrasonographic features were shape, orientation, margin, echo pattern, posterior features, calcifications, the vascularity of the masses and the presence of architectural distortions. The associations between those features and the intrinsic ILC subtypes were investigated.Results The most common manifestations of ILC on ultrasound (US) were hypoechoic masses with irregular shape, parallel orientation, spiculated margin, posterior acoustic shadowing, no calcification and blood vessels in the rim. The patients in the luminal A subtype were the youngest, and the patients in the HER2 overexpression subtype were the oldest (p = 0.01). On US, the HER2 overexpression subtype was characterized by microlobulated margins (p = 0.002), while the luminal A subtype and the luminal B subtype mostly had spiculated margins. The basal-like subtype was distinctive in that it had no posterior features (p = 0.041), rather than acoustic shadowing, and the masses in the HER2 and basal-like subtypes were larger than in the other two groups (p = 0.03).Conclusion There were significant differences and several trends in the ultrasonographic characteristics of different intrinsic subtypes, which may supply accurate imaging diagnostic criteria to assist in the management of individuals with ILC.
Keywords: invasive lobular carcinoma; ultrasound; BI-RADS; correlations; intrinsic subtype